2007
DOI: 10.1021/jf072360c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Aroma Compounds in Cooked Black Rice

Abstract: Black rice ( Oryza sativa L.), an aromatic specialty rice popular in Asia, has a unique flavor, the volatile chemistry of which has not been reported. The objectives of this research were to study volatile profiles of cooked black rice and to characterize the odor-active compounds. Thirty-five volatile compounds were identified by gas chromatography-mass spectrometry using a dynamic headspace system with Tenax trapping. Aldehydes and aromatics were quantitatively in the greatest abundance, accounting for 80.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 23 publications
6
109
3
1
Order By: Relevance
“…The volatiles detected in the cooked rice consisted of aldehydes, ketones, alcohols, heterocyclic volatiles, fatty acids, fatty esters, and phenolic volatiles ( Table 2). The results are consistent with previously reported rice volatiles extracted by different methods (Buttery et al, 1988;Jezussek et al, 2002;Widjaja et al, 1996;Yang et al, 2008aYang et al, , 2008b. One target m/z ion for each volatile was calculated as the method commonly used for metabolite profiling (Ochi et al, 2012), which provided relative levels of the volatiles, and not absolute quantities ( Table 2).…”
Section: Flavor Volatiles In Cooked Rice Of Varying Amylose Contentsupporting
confidence: 89%
“…The volatiles detected in the cooked rice consisted of aldehydes, ketones, alcohols, heterocyclic volatiles, fatty acids, fatty esters, and phenolic volatiles ( Table 2). The results are consistent with previously reported rice volatiles extracted by different methods (Buttery et al, 1988;Jezussek et al, 2002;Widjaja et al, 1996;Yang et al, 2008aYang et al, , 2008b. One target m/z ion for each volatile was calculated as the method commonly used for metabolite profiling (Ochi et al, 2012), which provided relative levels of the volatiles, and not absolute quantities ( Table 2).…”
Section: Flavor Volatiles In Cooked Rice Of Varying Amylose Contentsupporting
confidence: 89%
“…It is known that hexanal is produced nonenzymatically or by an unknown pathway from linoleic acid in rice 12,19,25 . Moreover, it was previously shown that aldehydes represent the highest percentage of total volatiles in cooked rice 24 , and dimethyl trisulfide has been identified as one of the compounds that make a significant contribution to the odour of rice cakes 3 . Accordingly, it is assumed that these aliphatic aldehydes and sulfide compounds were produced by steam heating, and were then reduced during the koji production process.…”
Section: Comparison Of Volatile Compounds In Steamed Rice and Rice Kojismentioning
confidence: 99%
“…Benzaldehyde showed relatively high contents among the aromatic compounds detected. The relative abundance of 2-pentylfuran was up to 279.58 μg/kg, showing high concentration similar to rice when compared with other volatiles contained in individual samples [7]. Simultaneously, 2-pentyl-furan, benzaldyhyde and 2-Methoxy-4-vinylphenol contributes to the unique roasted and nutty aroma [14].…”
Section: Resultsmentioning
confidence: 94%
“…A total of nine aldehydes were detected, with the levels ranging from not found to 802.29 μg/kg. The major aldehydes with high concentration included hexanal, heptanal, pentanal, nonanal, decanal, and octanal, which are also the commonly found in different cultivars of polished rice or BR [6], [7], suggesting that GBR retains the qualitatively similar flavor profiles even after germination by soaking in water for a certain duration. It was worth noting that aldehyde compounds often give grass and fresh odor at a sufficiently low concentration in the samples, but high levels of these compounds lead to the sniffing of rancidity.…”
Section: Resultsmentioning
confidence: 94%